Chemical composition and apparent digestibility of taro tubers processed by solid-state fermentation (SSF) in growing pigs - Caicedo, Willan (2019)
The chemical composition and apparent digestibility of nutrients of the solid-state fermentation (SSF) of waste taro tubers (Colocasia esculenta (L) Schott) inoculated with natural yogurt fed to growing pigs was determined. Dry matter (DM), organic matter (OM), crude protein (CP), crude fibre (CF), ash, ether extract (EE), nitrogen-free extracts (NFE) and gross energy (GE) were determined. For the study of apparent digestibility of the MS, MO, CP, CF, NFE and GE, 12 castrated Landrace x Duroc x Pietrain male pigs of 25 ± 2 kg were used, distributed in three groups with four animals each and fed with diets containing 0, 10, and 20% of SSF (T0, T10 and T20, respectively). The SSF presented high content of DM (83.33%), OM (93.77%), CP (13.95%), NFE (72.78%) and GE (4162.13 kcal kg MS-1) and low levels of EE (1.50%), CF (5.54%) and ashes (6.23%). The highest digestibility coefficients of the DM (91.37%), OM (96.36%), CP (87.81%) and CF (54.75%) were obtained in the T20 diet (p<0.05). There were no significant differences for NFE and GE digestibility. In conclusion, taro tubers processed by SSF and incorporated into the diet of growing pigs at 10 and 20% did not negatively affect the apparent digestibility of DM, OM, CP, CF, NFE and GE, which guarantees a food of adequate nutritional characteristics for pigs.